2014
DOI: 10.1111/joss.12127
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Drivers of Purchase Intent and Consumer Satisfaction of Chicken Eggs Using Principal Component Analysis and the Kano Model

Abstract: Twenty egg product attributes considered important by consumers (n = 400) were identified and their contribution to the satisfaction of quality requirements and purchase intent was examined using principal component analysis and the Kano model. Consumers considered freshness, absence of cracks, sale price and label stating "packing/best-before-date" as key attributes affecting purchase intent. Five principal components (PC1-PC5) were extracted, altogether explaining 57.43% of the total variance. Based on the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…The presence and absence of 5 types of quality attributes of the egg product were utilized as stimuli to evoke and measure emotions. Egg attributes namely intrinsic, aesthetic, extrinsic, expediency, and wholesome/safety, each a collective grouping of various quality characteristics as described by Wardy and others (a), were evaluated (see footnote of Table for description of egg quality attributes).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence and absence of 5 types of quality attributes of the egg product were utilized as stimuli to evoke and measure emotions. Egg attributes namely intrinsic, aesthetic, extrinsic, expediency, and wholesome/safety, each a collective grouping of various quality characteristics as described by Wardy and others (a), were evaluated (see footnote of Table for description of egg quality attributes).…”
Section: Methodsmentioning
confidence: 99%
“…The egg industry, therefore, occupies an important niche in the global food supply. Eggshell quality attributes encompass shell color, size, shell deformation, shell thickness, and ultrastructure among others, while interior quality is based on albumen quality, perivitelline membrane, yolk quality, and the presence of blood spots (Stadelman ; Roberts ; Wardy and others , a, b). However, for chicken eggs at the point of sale, consumer appraisals of quality that evoke emotions may be influenced more by the extrinsic eggshell quality and stated benefits, rather than the internal quality.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al (2013) used the Kano model in conjunction with conjoint analysis to understand consumer perspectives for chocolate milk and found agreement between positive Kano classifiers and higher utility values. Kano model analysis has also been applied to numerous other food and beverage products including black beans, eggs, and cottage cheese (Kuo et al, 2014;Wardy et al, 2014;Hubbard et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Based on its contribution, Indonesian Government regulates chicken meat and egg as staple-food commodities; to provide the availabilities of chicken meat and egg throughout the year at affordable prices. Previous study found that lower sale prices and larger egg sizes determine consumer preference (Wardy et al, 2014). Government issued regulation to facilitate the upstream poultry-industry investment in Indonesia to provide poultry-production input, such as feed, equipment, medicine, and other supporting businesses, of poultry farmers.…”
Section: Introductionmentioning
confidence: 99%